Implementation of Banana Juice Administration in Increasing Potassium with Hypokalemia History of CVD Infarction on the 6th Floor of the Darmawan Pavilion, Gatot Soebroto Army Hospital - Basuki, F.Dwi (Akademi Keperawatan RSPAD Gatot Soebroto, 2021)
Hypokalemia is a condition of blood potassium concentration below 3.5 mEq/L caused by a decrease in the total amount of potassium in the body or a disruption in the movement of potassium ions into cells and changes in the activity of the endogenous sympathetic nervous system. Cardiovascular disease (CVD) is a disorder of the heart and blood vessels. The design method of this study is descriptive using a case study approach. This study was taken on the 6th floor of the Darmawan Pavilion, Gatot Soebroto Army Hospital, with one client diagnosed with Electrolyte Imbalance Disorders related to regulatory mechanism disorders. Based on the results of the case study between the case and the research journal, it was found that clients who experienced Hypokalemia with a history of CVD infarction had a gap or difference in nursing problems. Between the case and the research journal, there was an intervention gap in the case study of electrolyte management, namely Hypokalemia, then implementation was carried out and the results were obtained at the time of evaluation, namely the problem was resolved. Based on the results of the case study conducted at the Darmawan Pavilion, 6th Floor, Gatot Soebroto Army Hospital, the application of banana juice to patients with hypokalemia. The results of this study are supported by the results of research by Edy Waliyo, Nopriantini, Shelly Festilia Agusanty.